Towards water-conscious green hydrogen and methanol production: A techno-economic review - Henrik Wenzel; Gian Müller; Freia Harzendorf; Thomas Schöb; Felix Kullmann; Jann Michael Weinand; Detlef Stolten (Nexus)
Summary: To enable a sustainable and socially accepted hydrogen and methanol economy, it is crucial to prioritize green and water-conscious production. In this review, we reveal a significant research gap regarding comprehensive assessments of such production methods. We present an innovative process chain, consisting of adsorption-based direct air capture, solid oxide electrolysis, and methanol synthesis to address this issue. To allow future comprehensive techno-economic assessments, we perform a systematic literature review and harmonization of the techno-economic parameters of the process chain’s technologies. Based on the conducted literature review, we find that the long-term median specific energy demand of adsorption-based direct air capture is expected to decrease to 204 kWhel/tCO2 and 1,257 kWhth/tCO2, while the capture cost is expected to decrease to 162 €2024/tCO2, with relative high uncertainty. The evaluated sources expect a future increase in system efficiency of solid oxide electrolysis to 80%, while the purchase equipment costs are expected to decrease significantly. Finally, we demonstrate the feasibility of the process chain from a techno-economic perspective and show a potential reduction in external heat demand of the DAC unit of up to 34% when integrated in the process chain. Broader context: To enable a sustainable and socially accepted hydrogen and methanol economy, it is crucial to prioritize green and water-conscious production. This is facilitated by the process chain presented, which also promotes social acceptance as excess water could be used for drinking water supply. By reviewing the techno-economic aspects of the process chain’s technologies on a detailed level, this work serves as a foundation for prospective comprehensive techno-economic assessments. Furthermore, as the investigated technologies direct air capture and solid oxide electrolysis generally experience a high level of interest, the conducted review enables modelers to investigate further systems on a detailed level. Finally, the water-conscious and green production of hydrogen and methanol will make the energy transition more sustainable, and regions that are abundant in renewable energy sources but suffer from water-scarcity will also be able to participate.